A randomized controlled trial to test the effectiveness of a peer-based social mobile game intervention to reduce smoking in youth. (December 2019) - Scholten, Hanneke; Luijten, Maartje; Granic, Isabela
Abstract: Smoking is a major cause of worldwide morbidity and mortality. Almost no evidence-based intervention programs are available to help youth quit smoking. We argue that ineffective targeting of peer influence and engagement difficulties are significant barriers to successful youth smoking cessation. To address these barriers, we developed the mobile game intervention HitnRun. A two-armed randomized controlled trial (RCT; n = 144) was conducted and young smokers ( M age = 19.39; SD age = 2.52) were randomly assigned to either play HitnRun or read a psychoeducational brochure. Prior to, directly following the intervention period, and after three-month follow-up, weekly smoking behavior, abstinence rates, intervention dose, and peer- and engagement-related factors were assessed. Results indicated similar reductions in weekly smoking levels and similar abstinence rates for both groups. Yet, we found a dose effect with HitnRun only: The longer participants played HitnRun, the lower their weekly smoking levels were. In the brochure group, a higher dose was related to higher weekly smoking levels at all measurement moments. Exploratory analyses showed the most powerful effects of HitnRun for participants who connected with and were engaged by the intervention. Future work should build on the promising potential of HitnRun by increasing personalization efforts and strengthening peer influence components.